Becoming Matter/Becoming Mother: Wilding in Ali Abbasi’s Border (Gräns) - Tschofen, Monique (Imaginations, 2023)
This paper provides an analysis of Ali Abbasi’s film Border through a feminist new materialist approach that centers what I call “wilding”—a process of worlding that challenges binary and rigid structures of thought that dichotomize existence into fixed categories through the cultivation of bewilderment, a state of openness to not-knowing which requires the unlearning of anthropocentric epistemologies. Paying attention to the etymological roots of the word “matter” (as body, wood, mother/nourishment, and place), the paper shows how the film displaces the dominion of sight with an emphasis on symbiosis that foregrounds the sense of touch